Moving Past the Status Quo: Redefining the Feedback Landscape for Junior Clinician-Educator Career Development - Jamie L. Geringer; David A. Lindholm; Brian E. Neubauer; Temple A. Ratcliffe (Journal of Medical Education and Curricular Development)
This perspective piece addresses the challenges junior clinician-educators face as they navigate career development within academic medical centers. In addition to understanding local promotion and tenure processes and seeking mentorship, we argue that faculty feedback is an often neglected, but essential, component in clinician-educator development. We repurpose and use the MISCA model—Message, Implementation, Student, Context, and Agents—as a framework to better understand and improve feedback for faculty. Crafting effective feedback messages, nurturing holistic growth, understanding contextual dynamics, acknowledging diverse feedback agents, and recognizing learner characteristics are key components of this model. Within each element of MISCA, we interpret how this model applies to clinician-educators and provide practical examples. We propose that combining insights around feedback derived from MISCA, with mentorship and frameworks for faculty competence, offers individuals and institutions opportunities to transform how they grow and develop faculty.